Endocrine disrupting potential of replacement flame retardants - Review of current knowledge for nuclear receptors associated with reproductive outcomes - Bajard, Lola; Negi, Chander K; Mustieles, Vicente; Melymuk, Lisa; Jomini, Stéphane; Barthelemy-Berneron, Johanna; Fernandez, Mariana F; Blaha, Ludek (Environment international, 2021)
BACKGROUND AND AIM: Endocrine disrupting chemicals (EDCs) constitute a major public health concern because they can induce a large spectrum of adverse effects by interfering with the hormonal system. Rapid identification of potential EDCs using in vitro screenings is therefore critical, particularly for chemicals of emerging concerns such as replacement flame retardants (FRs). The review aimed at identifying (1) data gaps and research needs regarding endocrine disrupting (ED) properties of replacement FRs and (2) potential EDCs among these emerging chemicals. METHODS: A systematic search was performed from open literature and ToxCast/Tox21 programs, and results from in vitro tests on the activities of 52 replacement FRs towards five hormone nuclear receptors (NRs) associated with reproductive outcomes (estrogen, androgen, glucocorticoid, progesterone, and aryl hydrocarbon receptors) were compiled and organized into tables. Findings were complemented with information from structure-based in silico model predictions and in vivo information when relevant. RESULTS: For the majority of the 52 replacement FRs, experimental in vitro data on activities towards these five NRs were either incomplete (15 FRs) or not found (24 FRs). Within the replacement FRs for which effect data were found, some appeared as candidate EDCs, such as triphenyl phosphate (TPhP) and tris(1,3-dichloropropyl)phosphate (TDCIPP). The search also revealed shared ED profiles. For example, anti-androgenic activity was reported for 19 FRs and predicted for another 21 FRs. DISCUSSION: This comprehensive review points to critical gaps in knowledge on ED potential for many replacement FRs, including chemicals to which the general population is likely exposed. Although this review does not cover all possible characteristics of ED, it allowed the identification of potential EDCs associated with reproductive outcomes, calling for deeper evaluation and possibly future regulation of these chemicals. By identifying shared ED profiles, this work also raises concerns for mixture effects since the population is co-exposed to several FRs and other chemicals.
Keywords: Reproduction; Endocrine Disruptors; ToxCast; endokrinní disruptory; rozmnožování; Flame Retardants; Emerging contaminants; Flame retardants; Phosphates; lidé; Endocrine disruption; Nuclear receptors; Steroid hormones; fosfáty; Receptors, Cytoplasmic and Nuclear; retardanty hoření; receptory cytoplazmatické a nukleární; Humans